Developing a Geospatial Public Facility Navigation Map for Assilulu, Indonesia Using ArcGIS - Fransina Latumahina; Rizka Regita Cahyani; Ruslin Ruslin; Rizky Nabilah N. I. F Handoyo (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to cultivate social responsibility among undergraduates of Pattimura University, Ambon, through the development of a Public Facility Navigation Map for Assilulu, a community in the Maluku Tengah district. Leveraging geographic information system (GIS) software, ArcGIS, the initiative gathered geospatial data through site surveys to obtain coordinates of key public infrastructure. This data was subsequently documented, tested for accuracy using Google Earth, and analyzed using ArcGIS 10.7. The resulting map was printed as banners and strategically placed at community entry points. This project contributes significantly to facilitating easier navigation for newcomers to the community, enabling them to locate important facilities such as government, religious, educational, and healthcare institutions, and tourism sites more efficiently. However, the project acknowledges room for further refinement, such as including additional facilities like agricultural, marine, and market infrastructures, recommending these as directions for future work in improving community navigability and land use planning in Assilulu.Highlights: Fostering social responsibility via practical community projects. Effective use of ArcGIS and Google Earth for navigation map creation. Identified potential for future map improvements and land use planning. Keywords: Geospatial Data, Public Facility Navigation, Community Engagement, ArcGIS, Land Use Planning